A Novel Microduplication in the Neurodevelopmental Gene SRGAP3 That Segregates with Psychotic Illness in the Family of a COS Proband - Nicole K. A. Wilson; Yohan Lee; Robert Long; Karen Hermetz; M. Katharine Rudd; Rachel Miller; Judith L. Rapoport; Anjené M. Addington (Case Reports in Genetics)
Schizophrenia is a debilitating mental disorder affecting approximately 1% of the world's population. Childhood onset schizophrenia (COS), defined as onset before age 13, is a rare and severe form of the illness that may have more salient genetic influence. We identified a ~134 kb duplication spanning exons 2–4 of the Slit-Robo GTPase-activating protein 3 (SRGAP3) gene on chromosome 3p25.3 that tracks with psychotic illness in the family of a COS proband. Cloning and sequencing of the duplication junction confirmed that the duplication is tandem, and analysis of the resulting mRNA transcript suggests that the duplication would result in a frame shift mutation. This is the first family report of a SRGAP3 copy number variant (CNV) in schizophrenia. Considering that SRGAP3 is important in neural development, we conclude that this SRGAP3 duplication may be an important factor contributing to the psychotic phenotype in this family.